2018
DOI: 10.1002/glia.23581
|View full text |Cite
|
Sign up to set email alerts
|

Regional and functional heterogeneity of antigen presenting cells in the mouse brain and meninges

Abstract: The central nervous system (CNS) is considered to be immune privileged, owing in part to the absence of major histocompatibility (MHC) class II + cells in the healthy brain parenchyma. However, systemic inflammation can activate microglia to express MHC class II, suggesting that systemic inflammation may be sufficient to mature microglia into functional antigen presenting cells (APCs). We examined the effects of systemic lipopolysaccharide (LPS)-induced inflammation on the phenotype and function of putative AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
4
16
0
Order By: Relevance
“…Accordingly, a higher concentration of CD4 + T lymphocytes was observed in the midbrain suggesting that an interplay between microglia and CD4 + T cells might occur in this region. Microglia with antigen-presenting properties are a rare cell type in the brain parenchyma, although a subpopulation of these cells was identified in the olfactory bulb after LPS stimulation [37]. Regionally heterogeneous gene expression profiles show that the transcriptome of cortical and striatal microglia differs from that of hippocampal microglia in genes involved in the immune response and in antigen presentation [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a higher concentration of CD4 + T lymphocytes was observed in the midbrain suggesting that an interplay between microglia and CD4 + T cells might occur in this region. Microglia with antigen-presenting properties are a rare cell type in the brain parenchyma, although a subpopulation of these cells was identified in the olfactory bulb after LPS stimulation [37]. Regionally heterogeneous gene expression profiles show that the transcriptome of cortical and striatal microglia differs from that of hippocampal microglia in genes involved in the immune response and in antigen presentation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Using different approaches, we demonstrate that LPS elicits a heterogeneous response in different brain regions. A context-dependent response of microglia to LPS has been described in the cortex and olfactory bulbs, even in the absence of morphological changes [37]. Flow cytometry analysis of thousands of CD45 low CD11b + cells indicated that the fraction of FCS hi /SSC hi microglia increases in all brain regions (from ≈ 5 to ≈ 20%), suggesting that approximately 15% of the cells in the brain parenchyma experienced morphological changes and do not respond homogenously to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in MNPs numbers is due to microglia proliferation, and monocyte infiltration in certain conditions [5,30]. A subpopulation of Cd11c + MNPs was also described [31,32]. Histological studies of human postmortem retinas suggest that subretinal MNPs are invariably present in intermediate and advanced (or 'late') forms of AMD [6,19,[33][34][35].…”
Section: Subretinal Space In Retinal Degenerative Statesmentioning
confidence: 99%
“…Nevertheless, numerous studies have reported that meningeal DCs survey the brain parenchyma and promote or constrain CNS immunity. This occurs through migration to the cervical lymph nodes and reactivation of T cells following their infiltration into the CNS (29)(30)(31)(32)(33)(34)(35). Tissue-resident DCs normally serve as phagocytes, but once activated, they process the Ag and carry it to lymph nodes where they function as potent APCs (36).…”
Section: Meningeal Lymphatics: From Anatomy To Central Nervous System Immune Surveillancementioning
confidence: 99%